Pengembangan Media Pembelajaran Mobile Learning Berbasis Android Pada Pembelajaran IPA di Kelas VIII SMP/MTs Tema Makananku Kesehatanku - Lukman Nulhakim; Adi Nestiadi; Desma Laelasari (PendIPA Journal of Science Education, 2023)
This research was conducted because of the difficulties experienced by students in learning, especially in the use of learning resources, teaching materials, or learning tools in the classroom. The conclusion of the interview with the resource person, namely the eighth grade science teacher, was that the learning resources available at school, especially for natural science learning, are still very minimal. Student books, student worksheets, and power points are still often used by teachers to deliver learning materials. WhatsApp is one of the technological intermediaries that students must use to learn independently during pandemic conditions, so students do not understand the material presented, especially science. This affects the process, objectives, and learning outcomes of students. In addition, the delivery of learning materials has not been integrated, so it takes a long time to develop one basic competency. The purpose of this study is to determine the validity of android-based mobile learning media for science learning in grade 8 (grade eight) junior high school or MTs with the theme of "my food, my health." The Borg and Gall R&D model was adapted by Sugiyono and modified by the author into five stages, including potential and problems, collecting data, designing products, validating product designs, and improving final product designs. Based on the results of data analysis, the expert validation score is included in the "very valid" category and can be used in science learning, with a percentage of findings of 84% from the results of material validation, 84.8 percent from media validation, and 86.6 percent from teacher assessment.